Associations between vaginal bacteria implicated in HIV acquisition risk and proinflammatory cytokines and chemokines. (13th June 2019) - Sabo, Michelle C; Lehman, Dara A; Wang, Bingjie; Richardson, Barbra A; Srinivasan, Sujatha; Osborn, Lusi; Matemo, Daniel; Kinuthia, John; Fiedler, Tina L; Munch, Matthew M; Drake, Alison L; Fredricks, David N; et al.
Abstract : Objectives: Recent studies have identified vaginal bacterial taxa associated with increased HIV risk. A possible mechanism to explain these results is that individual taxa differentially promote cervicovaginal inflammation. This study aimed to explore relationships between concentrations of bacteria previously linked to HIV acquisition and vaginal concentrations of proinflammatory cytokines and chemokines. Methods: In this cross-sectional analysis, concentrations of 17 bacterial taxa and four proinflammatory cytokines (interleukin (IL)-1β, IL-6, IL-10 and tumour necrosis factor alpha (TNFα)) and two proinflammatory chemokines (IL-8 and interferon gamma-induced protein 10) were measured in vaginal swabs collected from 80 HIV-uninfected women. Cytokine and chemokine concentrations were compared between women with bacterial concentrations above or below the lower limit of detection as determined by quantitative PCR for each taxon. Principal component analysis was used to create a summary score for closely correlated bacteria, and linear regression analysis was used to evaluate associations between this score and increasing concentrations of TNFα and IL-1β. Results: Detection of Dialister micraerophilus (p=0.01), Eggerthella sp type 1 (p=0.05) or Mycoplasma hominis (p=0.03) was associated with higher TNFα concentrations, and detection of D. micraerophilus (p<0.01), Eggerthella sp type 1 (p=0.04), M. hominis (p=0.02) or Parvimonas sp type 2 (p=0.05) was associated with significantly higher IL-1β concentrations. Seven bacterial taxa ( D. micraerophilus, Eggerthella sp type 1, Gemella asaccharolytica, Sneathia sp, Megasphaera sp, M. hominis and Parvimonas sp type 2) were found to be highly correlated by principal component analysis (eigenvalue 5.24, explaining 74.92% of variability). Linear regression analysis demonstrated associations between this principal component and concentrations of TNFα (β=0.55, 95% CI 0.01 to 1.08; p=0.048) and IL-1β (β=0.96, 95% CI 0.19 to 1.74; p=0.016). Conclusions: This study provides evidence that several highly correlated vaginal bacterial taxa may influence vaginal cytokine and chemokine concentrations. These results suggest a mechanism where the presence of specific bacterial taxa could influence HIV susceptibility by increasing vaginal inflammation.